Fenomena Kaunan dalam Masyarakat Toraja Dari Perspektif Emmanuel Levinas - Dody Grace Febryanto Rongrean; Pius Pandor (Jurnal Filsafat Indonesia, 2023)
The focus of this study is to see and reveal how the relationship of kaunan in Toraja society is. The author wants to see why kaunan is looked down upon in a society that basically they are human beings who think and feel. and the author also wants to see how the relationships that are built in their despised condition are. does kaunan not have uniqueness? Aren't they also unique creations? What phenomenon makes them looked down on so low? The methodology used in this study is qualitative with a phenomenological approach, namely by allowing the subject to present himself as he is without any limiting ideas. Data were obtained by reading related literature and in-depth interviews. By using the perspective of Emmanuel Levinas, it will be seen how the causal relationality is. As the findings in this paper is that the relationship is a relationship of responsibility with the concept of family as responsibility for the presence of others. In line with what Levinas said, we must be responsible for the presence of the other (the other). Kaunan is looked down upon because of the universal idea. In the encounter between kaunan and To sugi', the relationship that is built is an asymmetrical relationship.